A comprehensive review in improving delivery of small-molecule chemotherapeutic agents overcoming the blood-brain/brain tumor barriers for glioblastoma treatment. (1st January 2019) - Wang, Da; Wang, Chao; Wang, Liang; Chen, Yue
Abstract: Glioblastoma (GBM) is the most common and lethal primary brain tumor which is highly resistant to conventional radiotherapy and chemotherapy, and cannot be effectively controlled by surgical resection. Due to inevitable recurrence of GBM, it remains essentially incurable with a median overall survival of less than 18 months after diagnosis. A great challenge in current therapies lies in the abrogated delivery of most of the chemotherapeutic agents to the tumor location in the presence of blood-brain barrier (BBB) and blood-brain tumor barrier (BBTB). These protective barriers serve as a selectively permeable hurdle reducing the efficacy of anti-tumor drugs in GBM therapy. This work systematically gives a comprehensive review on: (i) the characteristics of the BBB and the BBTB, (ii) the influence of BBB/BBTB on drug delivery and the screening strategy of small-molecule chemotherapeutic agents with promising BBB/BBTB-permeable potential, (iii) the strategies to overcome the BBB/BBTB as well as the techniques which can lead to transient BBB/BBTB opening or disruption allowing for improving BBB/BBTB-penetration of drugs. It is hoped that this review provide practical guidance for the future development of small BBB/BBTB-permeable agents against GBM as well as approaches enhancing drug delivery across the BBB/BBTB to GBM.